2015
DOI: 10.1364/ol.40.001639
|View full text |Cite
|
Sign up to set email alerts
|

On the dual-cone nature of the conical refraction phenomenon

Abstract: In conical refraction (CR), a focused Gaussian input beam passing through a biaxial crystal and parallel to one of the optic axes is transformed into a pair of concentric bright rings split by a dark (Poggendorff) ring at the focal plane. Here, we show the generation of a CR transverse pattern that does not present the Poggendorff fine splitting at the focal plane, i.e. it forms a single light ring. This light ring is generated from a non-homogeneously polarized input light beam obtained by using a spatially i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Recently it was proposed that the CR beam can be understood as the interaction of two light cones with slightly different positions of their vertices along the axial direction [59]. Our contribution to this picture has been the reformulation of the dual-cone model of CR and also the experimental demonstration of the existence of two light cones without the need of blocking the beam at any part [56]. A segmented linear polarizer that mimics the usual CR polarization distribution has been used in order to select each of the cones and modify the intensity ratio between the inner and the outer rings of CR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it was proposed that the CR beam can be understood as the interaction of two light cones with slightly different positions of their vertices along the axial direction [59]. Our contribution to this picture has been the reformulation of the dual-cone model of CR and also the experimental demonstration of the existence of two light cones without the need of blocking the beam at any part [56]. A segmented linear polarizer that mimics the usual CR polarization distribution has been used in order to select each of the cones and modify the intensity ratio between the inner and the outer rings of CR.…”
Section: Discussionmentioning
confidence: 99%
“…Note that alternatively Dreger [57] and Garnier [58] have reported the solutions of optical beam propagation in biaxial crystals, although in both cases the theory presented is very involved. On the other hand, Sokolovskii and co-workers showed that the Belsky-Khapalyuk-Berry equations can be re-arranged so that they describe CR in terms of the interference between two co-propagating cones [59], being this theory demonstrated experimentally and newly re-formulated by us [56], as it is shown in Section 2.4. Alternatively, we have also presented a novel proposal that can be used to easily predict the CR pattern at the focal plane by means of a wave-vector and polarization formalism [54] that can be also used in a cascade of biaxial crystals, as we have also shown in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, G.S.Sokolovskii et al 13 and later on A.Turpin et al 14 have shown that these equations can be transformed in a way enabling the electric displacement vector D to be written as:…”
Section: Background Theory and A Dual-cone Modelmentioning
confidence: 99%
“…Therefore, with M 2 >1 one should observe more than one dark ring in the Lloyd's plane. The results of numerical simulations with (14) for М …”
Section: Introduction Of the M 2 Parametermentioning
confidence: 99%